Modeling a Semiotic Process in the Immune System: Signal Transduction in B-cells Activation - Charbel Niño El-Hani; Argyris Arnellos; João Queiroza (tripleC: Communication, Capitalism & Critique)
Here, we present a semiotic model of signaling pathways in B-cells in order to substantiate the view that semiotic modeling is required for the referential aspect of signaling processes to be grasped. We discuss how a process of asymmetry-formation through membrane closing puts living systems under selection pressure to develop semiotic competence, and, thus, signaling becomes a key process in the interface between system and environment. We introduce a number of notions in Peirce’s theory of signs, giving emphasis to the explanation of semiosis as a dynamic process in which chains of triads are instantiated, and develop a semiotic model of signaling pathways in B-cells based on those notions. We offer new, semiotic tools to model signaling in living systems, explaining how the relation to the same external object is maintained throughout several changes in the material bases of signaling (i.e., signs) in such systems.